Inhibitability of compounds from lactuca indica L. towards enzyme alpha-glucosidase based on quantum chemical calculation and docking simulation - Nguyễn, Vĩnh Phú; Trần, Quang Huy; Phan, Tứ Quý; Bùi, Quang Thành; Nguyễn, Thị Thanh Hải; Nguyễn, Phú Tùng; Lê, Thị Kim Dung; Nguyễn, Quang Mẫn; Hoàng, Kim Anh Phụng; Nguyễn, Thị Ái Nhung (Hue University Journal of Science: Natural Science, 2025)
Abstract. Diabetes causes excessively high blood sugar levels and disrupts metabolism in the body. Inhibiting the α-glucosidase enzyme is one of the treatments for diabetes. In this study, the compounds from Lactuca indica L. in the n-hexane extract were screened in silico to identify potential inhibitors of the 3W37 protein of the α-glucosidase enzyme. Eleven compounds (1–11) from the extract were identified by using the GC-MS method. The geometric structures of these compounds were optimized, and their quantum parameters were determined with the natural bond orbital method. The binding sites 1 and 2 of the protein were identified as favourable for molecular docking, and the inhibitory potential of the compounds was ranked in descending order as follows: 3 > 8 > 10 > 5 > 7 > 6 > 11 > 4 > 1 > 9 > 2. These compounds comply with Lipinski’s Rule of Five and exhibit pharmacokinetic and toxicity properties, including good absorption, no hepatic metabolism, renal excretion, and safety for the human body. These results will guide experimental studies to develop new approaches for supporting diabetes treatment.